14^-4 = 1/14^4
think about it. 14^0 = 1
1/14^4 = 14^0/14^4 = 14^(0-4) = 14^-4
on the other hand, 14*(-4) = -56
#2 ok
#3 6^a x 6^v = 6^(a+v)
review the rules of exponents
#4 same as #3
7^5 x 7^6 = 7^(5+6) = 7^11
49^30 = 49^(5*6) = (49^5)^6
1.
Simplify.
14 ^ -4
A. 1 / 14 ^ 4
B. -56 ** ?
C. 1 / 14
D. 1 / 14 ^ -4
----
2.
Multiply, write in scientific notation.
(9 x 10^4)(8 x 10^6)
A. 7.2 x 10^25
B. 1.7 x 10^11
C. 7.2 x 10^11 ** ?
D. 1.7 x 10^25
----
3.
Write expression using single exponent.
6^a x 6^v
A. 6^a+v
B. 6^av
C. 36^av** ??
D. 36^a+v
----
4.
Write expression using single exponent.
7^5 x 7^6
A. 49^30 **?
B. 7^30
C. 49^11
D. 7^11
2 answers
Thank you!!